Safety of Off-Label Use of Anticancer Drugs in Oncology - E. V. Karabina; D. D. Sakaeva; O. N. Lipatov (Креативная хирургия и онкология, 2024)
Safety is recognized as a crucial issue of off-label use of anticancer drugs. The potential benefits of such prescriptions in oncology are associated with prevailing the expected clinical benefits over the risks of complications. However, in certain clinical situations with uncertain benefit/risk ratio, an off-label use of drugs may threaten the life and health of the patient. The present paper explores the safety of off-label anticancer drug therapy in real clinical practice. Health care and routine clinical practice are given particular emphasis on systematic recording and careful monitoring of adverse events associated with the off-label use of medicinal products. The creation of a unified registration system for off-label use of drug therapy in oncology along with the creation of large databases (on the sites of institutions with an option to combine the data obtained at the level of districts, regions and the country) enables a significant amount of information on the safety and effectiveness of this approach to be gathered. As a result, a predictable nature of treatment and manageable toxic effects are potentially provided. The study into reasons behind off-label use of drugs in oncology, as well as the study into spectrum and severity of adverse events resulting from the implementation of these prescriptions, will provide detailed information on the safety of off-label use of anticancer agents in patients with malignant neoplasms at different stages of oncological treatment.